Advance in Using Plasma Technology for Modification or Fabrication of Carbon‐Based Materials and Their Applications in Environmental, Material, and Energy Fields. (10th November 2020) - Sun, Xin; Bao, Jiacheng; Li, Kai; Argyle, Morris D.; Tan, Gang; Adidharma, Hertanto; Zhang, Kaihang; Fan, Maohong; Ning, Ping
Abstract: Plasma technology is an eco‐friendly way to modify or fabricate carbon‐based materials (CBMs) due to plasmas' distinctive abilities in tuning the surface physicochemical properties by implanting functional groups or incorporating heteroatoms into the surface without changing the bulk structure. However, the mechanisms of functional groups formation on the carbon surface are still not clearly explained because of the variety of different discharge conditions and the complexity of plasma chemistry. Consequently, this paper contains a comprehensive review of plasma‐treated carbon‐based materials and their applications in environmental, materials, and energy fields. Plasma‐treated CBMs used in these fields have been significantly enhanced in recent years because these related materials possess unique features after plasma treatment, such as higher adsorption capacity, enhanced wettability, improved electrocatalytic activity, etc. Meanwhile, this paper also summarizes possible reaction routes for the generation of functional groups on CBMs. The outlook for future research is summarized, with suggestions that plasma technology research and development shall attempt to achieve precise control of plasmas to synthesize or to modify CBMs at the atomic level. Abstract : Plasma treatment for carbon‐based materials (CBMs) has great merits in that plasma technology can alter the surface physicochemical properties by implanting functional groups or incorporating heteroatoms without changing the bulk structure. CBMs in different plasma treatment atmospheres can obtain tailored surface physicochemical properties, thus the different CBMs modified or fabricated can be used in environmental abatement, materials science, and energy storage.